Income contingent tuition fees for universities. - Shephard, N (Department of Economics (University of Oxford), 2009)
I show that the fiscal position of the UK means it will be very hard for the next government to allow the undergraduate fee cap to increase beyond the rate of inflation. The funding postion of the higher education sector can be improved by the government removing the interest rate subsidy it currently gives to students. However, even this does not really allow the fee cap to increase markedly as any increase would lead to the Government’s loan book expanding. I suggest each university should be allowed to introduce its own income contingent fee, on top of the existing national funding structure. Each graduate would only have to pay these fees to its university if their income rises beyond the point of paying off their maintenance and state tuition loans. I show these new fees are fiscally neutral and have no impact on the loan book or the financial position of the universities which do not introduce such fees. Such fees have the potential to provide a long-run solution to the repeated underfunding of undergraduate education at a number of English universities and reduce the fiscal pressure the state is under.